Influence of climatic factors on the medical attentions of dermatologic diseases in a hospital of Lima, Peru Influência de fatores climáticos no tratamento médico de doenças dermatológicas em um hospital em Lima, Peru - Ericson L. Gutierrez; Carlos Galarza; Willy Ramos; Maybbe Mendoza; María E. Smith; Alex G. Ortega-Loayza (Sociedade Brasileira de Dermatologia, 2010)
BACKGROUND: Significant associations have been described between climatic factors and human health, which can occur in dermatologic diseases too. OBJECTIVE: To determine the influence of the climatic factors on the medical attentions of dermatologic diseases in a general hospital in Lima (Peru). PATIENTS AND METHODS: Observational study which was carried out in a national hospital between January 2004 and December 2007. The diagnoses were classified according to the ICD-10 system. The climate information was provided by the National Oceanographic and Atmospheric Administration from USA(NOAA). RESULTS: 3 294 patients were included in the study, the average age was 35.4 ± 20.7 years old, and 53.2% were females. The "El Niño" phenomenon was associated with an increase in the prevalence of actinic keratosis (p=0.002), viral warts (p=0.001) and rosacea (p=0.014). The "La Niña" phenomenon was associated with a reduction in viral warts (p=0.026). Spring was associated with an increase of dermatitis (p=0.003), and summer was associated with an increase of benign neoplasms (p=0.049). CONCLUSION: The climatic variations influenced the occurrence of certain dermatologic diseases. The present study may represent an orientation guide to specialists and general practitioners identifying the most common dermatologic diagnoses and thus enabling better preparation to treat these cases in determined seasons of the year. FUNDAMENTO: Associações significativas entre fatores climáticos e saúde humana têm sido descritas, inclusive na área de Dermatologia. OBJETIVO: Determinar a influência de fatores climáticos no tratamento de doenças dermatológicas em um hospital em Lima (Peru). PACIENTES E MÉTODOS: Estudo observacional realizado em um hospital em Lima entre janeiro de 2004 e dezembro de 2007. Os diagnósticos foram classificados de acordo com o sistema ICD-10. Informações climáticas foram fornecidas pela "National Oceanographic and Atmospheric Administration" (NOAA - USA). RESULTADOS: 3.294 pacientes participaram do estudo. A idade media foi 35.4 ± 20.7 anos e 53,2% eram mulheres. O fenômeno "El Niño" foi associado a um aumento da prevalência de queratose actínica (p=0,002), verrugas virais (p=0,001) e rosácea (p=0,014). O fenômeno "La Niña" foi associado a diminuição das verrugas virais (p=0,026). A primavera foi associada a um aumento de dermatite (p=0,003) e o verão, a um aumento de tumores benignos (p=0,049). CONCLUSÃO: Variações climáticas influenciam o aparecimento de algumas doenças dermatológicas. O presente trabalho pode orientar especialistas e clínicos gerais por meio da identificação dos diagnósticos dermatológicos mais comuns e, consequentemente, prepará-los para tratar doenças sazonais.